Ultrasound Guided Intra-Articular Injection of Triptolide-loaded Solid Lipid Nanoparticle for Treatment of Antigen-Induced Arthritis in Rabbits - Li, Shilin; Su, Liyang; Lv, Guorong; Luo, Weiwen; Kang, Yishan (Frontiers in Pharmacology, 2022)
Objective: To evaluate the efficacy of ultrasound-guided intra-articular injection of triptolide-loaded solid lipid nanoparticle (TP-SLN) for treatment of antigen-induced arthritis (AIA) in rabbits. Material and methods: Knee joints of 33 New Zealand rabbits with AIA were injected intra-articularly with triptolide (TP), TP-SLN, betamethasone (BS) and dimethyl sulfoxide (DMSO). The remaining 6 rabbits were untreated as the control group. The injection therapy in intervention groups was initiated one week after the last immunization in order to avoid irreversible joint damage in the later induction. The efficacy and side effects of each group were determined by combining ultrasonic scores, pathological scores, behavior, appetite, weight, joint diameter, skin temperature and biochemical examination. Results: With the exception of the DMSO group, the interventions were effective in treating synovitis compared with the control group, with TP-SLN and BS being the best. The ultrasonic and pathological scores in synovitis of the TP group were lower than that of model group (Z = -2.726 and -2.530, P ＜ 0.05). The ultrasonic scores differed significantly between BS group and TP-SLN group (Z = -2.17 and -2.360, respectively, P < 0.05) and pathological scores (Z = -2.687 and -2.082, respectively, P < 0.05). Compared with the control group, the TP, BS and TP-SLN were all effective in treating synovial blood flow and bone erosion and there were no significant differences of ultrasonic and pathological scores among them (P > 0.05). The ultrasonic scores of synovial blood flow (Z = -3.033, -2.842, -3.277, P ＜ 0.01) were lower than in the controls. The ultrasonic scores (Z = -2.948, -3.141, -3.210, P ＜ 0.01) and pathological scores (Z = -2.216, -2.505, -2.505, P ＜ 0.05)of bone erosion were also lower than in the model group. Conclusions: The therapeutic effect of TP-SLN on arthritis is better than that of TP, but there is no difference between BS and TP-SLN. Therefore, TP-SLN may be used as an alternative to BS in the treatment of rheumatoid arthritis in the future.